The Killing of Tlatelolco: Comparing and Contrasting Carlos Monsiváis’s Chronicle with Elena Poniatowska’s Testimony and the Printed Media’s (Anclajes, 2019)
This work proposes the analysis and interpretation of the main narrative procedures of the chronicles of Carlos Monsiváis around the massacre of 1968, to then compare and contrast them, from their interdiscursive remissions with those of his colleague and contemporary Elena Poniatowska, and with other journalistic reports published by the main Mexican newspapers. The analysis of tones, strategies and writing grammars of Monsiváis himself versus Poniatowska's discourse allows us to establish differences to verify different ways of exercising the urban chronicle. Likewise, we propose to problematize the position of the chroniclers in relation to the construction that the mass media made of the events and representations around 1968, and analyze the way in which each of them included the testimony of the witnesses.
Keywords: Chronicles; literature; journalism; procedures; Tlatelolco